Si nanowires for antireflective coatings of photovoltaic cells - Druzhinin, A.; Ostrovskii, I.; Yerokhov, V.; Khoverko, Yu.; Nichkalo, S.; Kogut, Iu. (Видавництво Львівської політехніки, 2012)
The paper deals with investigation of CVD grown silicon nanowires fabrication for antireflective coatings of photovoltaic cells.
Keywords: nanowire; photovoltaic cell; antireflective coating